Strawberry tree honey as a new potential functional food. Part 2: Strawberry tree honey increases ROS generation by suppressing Nrf2-ARE and NF-кB signaling pathways and decreases metabolic phenotypes and metastatic activity in colon cancer cells. (June 2019) - Afrin, Sadia; Forbes-Hernández, Tamara Y.; Cianciosi, Danila; Pistollato, Francesca; Zhang, JiaoJiao; Pacetti, Mattia; Amici, Adolfo; Reboredo-Rodríguez, Patricia; Simal-Gandara, Jesus; Bompadre, Stefano; Quiles, Josè L.; Giampieri, Francesca; et al.
Graphical abstract: Highlights: STH induces oxidative stress and decreases antioxidant defenses in colon cancer cells. STH suppresses NF-кB, p-IкBα and Nrf2 expression in colon cancer cells. STH decreases mitochondrial respiration and glycolysis in colon cancer cells. STH inhibits colon cancer cell migration, invasion and EMT. Abstract: The aim of the present study was to evaluate the effects of Strawberry tree honey (STH) on oxidative stress, metabolic phenotype, migration, invasion and epithelial-mesenchymal transition in adenocarcinoma (HCT-116) and metastatic (LoVo) colon cancer cells as well as in human dermal fibroblasts (HDF). Significant oxidative stress was observed through the increase of intracellular ROS generation, lipid and protein damage and reduction of antioxidant enzyme activities in colon cancer cells; in HDF these effects were limited or none. The expression of NF-кB, p-IкBα, Nrf2 was suppressed after STH treatment in colon cancer cells. All the parameters of mitochondrial respiration and glycolysis were reduced after STH treatment in cancer cells, while they were unchanged in HDF. Wound-closure percentages and the expression of MMP-2, MMP-9, N-cadherin, β-catenin decreased, while those of E-cadherin increased after STH treatment in colon cancer cells. Thus, STH can be used for its potential in cancer prevention.